Implementation supply chain management concept in the industrial symbiosis of the fragrant lemongrass distillation. Issue 4 (April 2020) - Aviasti, A; Amaranti, R; Nugraha, N
Abstract: The citronella oil refining industry contributes greatly to improving the community's economy. In the supply chain of citronella oil, the community usually acts as a supplier (fragrant lemongrass farmers), manufacturers (distillers of citronella oil), and distributors (collectors of citronella oil). The main problem in the citronella oil refining industry is the uncertainty of the supply chain. Fragrant lemongrass supply chain mapping is done to determine the capacity and needs of all actors involved from raw material sources to retail consumers. Thus, the continuity of fragrant lemongrass supplies increased production capacity in refineries, and market potential can be estimated more precisely. On the other hand, integration between industries is needed to prevent the impact of environmental damage while increasing profits. The symbiosis model of the citronella refining industry is expected to optimize the potential and existing resources through an industrial system that is efficient, integrated, easy to implement, and environmentally sound. This paper will discuss how the application of supply chain management concepts in the symbiosis of the citronella refining industry so that the objectives of cooperation in the environmentally sound supply chain can be realized.